2011
DOI: 10.12973/ejmste/75194
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Biology Teachers’ and Primary School Students’ Attitudes Toward and Knowledge about Snakes

Abstract: Snakes are controversial animals emblazoned by legends, but also endangered as a result of human prejudice and fear. The author investigated gender and age-related differences in attitudes to and knowledge of snakes comparing samples of school children and preservice teachers. It was found that although pre-service teachers had better knowledge of and more positive scientistic and moralistic attitudes toward snakes fear of snakes and willingness to pay for snake conservation was no statistically different betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 26 publications
(31 reference statements)
0
13
0
1
Order By: Relevance
“…In comparison, Prokop and Tunnicliffe (2008) found the effect of knowledge only on the attitudes toward non-feared animals (bats), but not phobia-related animals such as spiders. The authors argued that public awareness is not enough to improve attitudes toward animals that were associated with danger in human evolutionary history, and Tomažič (2011) found that knowledge of snakes does not affect fear of these animals. However, biologically educated people do not necessarily need to have a higher knowledge than non-biologists (Tomažič, 2011), and it is thus possible that it was rather their higher experience with live animals that affected the scores (Ballouard et al, 2012).…”
Section: Contribution Of Fear and Disgust To Snake Fearmentioning
confidence: 99%
“…In comparison, Prokop and Tunnicliffe (2008) found the effect of knowledge only on the attitudes toward non-feared animals (bats), but not phobia-related animals such as spiders. The authors argued that public awareness is not enough to improve attitudes toward animals that were associated with danger in human evolutionary history, and Tomažič (2011) found that knowledge of snakes does not affect fear of these animals. However, biologically educated people do not necessarily need to have a higher knowledge than non-biologists (Tomažič, 2011), and it is thus possible that it was rather their higher experience with live animals that affected the scores (Ballouard et al, 2012).…”
Section: Contribution Of Fear and Disgust To Snake Fearmentioning
confidence: 99%
“…Until now, many research studies assessing attitudes or perceptions towards different animal species were performed. They were focusing either on the animals that are disliked such as invertebrates (Kellert, 1993;Killermann, 1996), spiders, bats, snakes (Prokop, Özel, & Uşak, 2009;Tomažič, 2011a), endangered, i.e. amphibians…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide there are few studies on the topic, and existing ones are mainly concentrated in Africa [ 38 - 40 ], south America [ 41 - 45 ], and Asia [ 46 - 49 ]. In Europe these types of studies are very rare [ 50 - 52 ] and in Portugal, apart from some anecdotal references in some herpetological publications or in old general ethnographic studies, there are also few studies on the topic [ 24 , 35 , 36 ]. Studies presenting situations in which this type of knowledge has a negative impact on conservation are few, and almost none have ever established a clear link between the presence of folklore, negative values, and preferences and persecution and anti-conservation attitudes towards reptiles.…”
Section: Introductionmentioning
confidence: 99%